2013
DOI: 10.1042/bj20130317
|View full text |Cite
|
Sign up to set email alerts
|

Structure-guided optimization of protein kinase inhibitors reverses aminoglycoside antibiotic resistance

Abstract: SYNOPSIS Activity of the aminoglycoside phosphotransferase APH(3’)-Ia leads to resistance to aminoglycoside antibiotics in pathogenic Gram-negative bacteria, and contributes to the clinical obsolescence of this class of antibiotics. One strategy to rescue compromised antibiotics such as aminoglycosides is targeting the enzymes that confer resistance with small molecules. Previously we demonstrated that eukaryotic protein kinase (ePK) inhibitors could inhibit APH enzymes, due to the structural similarity betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 53 publications
0
62
0
Order By: Relevance
“…Motivated by the prior success of this approach, considerable efforts to develop new beta-lactamase inhibitors are underway and several such inhibitors are currently in clinical trials [53]. New compounds inhibiting enzymes conferring resistance to carbapenem beta-lactams and aminoglycosides were identified by screening natural products from environmental microorganisms [54 ] and using a structure-guided approach [55], respectively. In both cases, the identified compounds were previously known for entirely different activities on plant leaves and as eukaryotic protein kinase inhibitors, respectively, highlighting the potential for repurposing drugs.…”
Section: Combinations Of Antibiotics With Other Compoundsmentioning
confidence: 99%
“…Motivated by the prior success of this approach, considerable efforts to develop new beta-lactamase inhibitors are underway and several such inhibitors are currently in clinical trials [53]. New compounds inhibiting enzymes conferring resistance to carbapenem beta-lactams and aminoglycosides were identified by screening natural products from environmental microorganisms [54 ] and using a structure-guided approach [55], respectively. In both cases, the identified compounds were previously known for entirely different activities on plant leaves and as eukaryotic protein kinase inhibitors, respectively, highlighting the potential for repurposing drugs.…”
Section: Combinations Of Antibiotics With Other Compoundsmentioning
confidence: 99%
“…The vector pKOV-dxrS222T was created by cutting a 2,875-bp BamHI/PstI fragment from the vector pACYC-dxrS222T and ligating it into pKOV, after removal of the 2,036-bp BamHI/PstI fragment. The pKOVdxrS222T vector was used to transform either E. coli MG1655 or E. coli BW25113 ⌬bamB⌬tolC (a kind gift of Gerard Wright, McMaster University, Ontario, Canada) (44). Colonies were grown on LB with either 30 g/ml (for MG1655) or 6 g/ml (for BW25113 ⌬bamB⌬tolC) of chloramphenicol at 30°C for 48 to 72 h. Colonies were picked and grown overnight at 42°C in LB at the appropriate concentration of chloramphenicol.…”
Section: Generation Of Mutant Libraries Of E Coli Dxr and Ispdmentioning
confidence: 99%
“…Therefore, we replaced the native dxr locus with dxr-S222T in the efflux-defective E. coli strain BW25113 ⌬bamB⌬tolC (44). In this strain, as in MG1655, expression of the dxr-S222T allele confers substantial resistance to FSM (EC 50 s, 0.37 M [95% CI, 0.22 to 0.64 M] versus 5.0 M [95% CI, 2.4 to 11 M] for BW25113 ⌬bamB⌬tolC and BW25113 ⌬bamB⌬tolC-dxr-S222T, respectively; t test, P Ͻ 0.0005) (Fig.…”
Section: Identification Of Fsm Resistance Alleles Of Dxr But Not Ispdmentioning
confidence: 99%
“…Similarly, molecular docking study of known APH inhibitors, ie, apigenin, quercetin, damnacanthal, genistein, LYS294002, SB203580, and virtually screened inhibitor ZINC71575479 was performed with APH model using AutoDock 4.2 to explore the inhibition mechanism of APH from B. cereus . The virtually screened inhibitor ZINC71575479 was investigated from our earlier study, which showed efficient binding ability toward NTP‐binding site of various aminoglycoside kinases from different multidrug‐resistant strains .…”
Section: Methodsmentioning
confidence: 99%